A Novel Concept to Produce Super Soft Characteristic Ring-yarn with Structural Variation via Against-twisting. Issue 13 (1st December 2022) - Duo, Xu; Fan, Han; Li, Jian; Gao, Chong; Yang, Wangwang; Xu, Weilin; Liu, Keshuai
ABSTRACT: In this study, a novel concept has been introduced as a structural varied against-twisting method to produce super soft characteristic yarn with low residual torque. Geometrical analysis indicated that the regular intervention of reverse twist stress remodeled the fiber arrangements in yarn structure, causing fiber motion trace variations from the original concentric helix to the deformed nonconcentric helix with the emergence of reversed fiber segments. The mechanical property prediction revealed the wet snarlings of against-twisted yarn with lower inclination angle on yarn apparent structure was much smaller than the less-twisted yarn with same twists. Then, the systematical comparison was then conducted between against-twisted yarn produced by the twice twisting process and less-twisted yarns spun with twist reduction, which showed that against-twisted yarns have lower residual torque and higher yarn strength than that of less-twisted yarns. However, the against-twisted yarns have a fluffy structure with more hairiness.